The nature and management of breakdown in foster care placements: developing preliminary management guidelines - Whitaker, Penelope Dorothy (Department of Social Development, 2024)
This research study was conducted at a child welfare agency in Cape Town and has focused on the nature and management of foster care breakdown. A preliminary set of guidelines was developed as an aid to effective management. Foster care is an important part of any child welfare service programme. It is based on the premise that a family still provides the best environment for the development of a child (Foster Care Charter: 1987). In an effort to achieve this purpose, foster care has become an increasingly complex task focusing on working contracts, reconstruction work, time limited intervention, behaviour programmes and effective, comprehensive management of the foster placement. An area which seems to be overlooked is the development of appropriate guidelines to deal with foster placement breakdown.